2023
DOI: 10.1039/d2qm01287a
|View full text |Cite
|
Sign up to set email alerts
|

Carbon-based designer and programmable fluorescent quantum dots for targeted biological and biomedical applications

Abstract: Carbon dots (CDs) are emerging nanobiomaterials owing to their exceptional optical and physio-chemical properties. In recent years, they have gained attention due to some of their distinctive applications in biological...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 182 publications
(229 reference statements)
0
15
0
Order By: Relevance
“…[221][222][223] Nanosized carbon cores containing conjugated p-domains with signicant functional groups produce multicolour uorescence due to the quantum connement effect, one of the main mechanisms among the others. [224][225][226] It is plausible to tweak the characteristic bandgap transition by modifying the size of the p-domains. The increase in the size of the p-domain carbon core causes a smaller bandgap.…”
Section: Quantum Connement Effectmentioning
confidence: 99%
“…[221][222][223] Nanosized carbon cores containing conjugated p-domains with signicant functional groups produce multicolour uorescence due to the quantum connement effect, one of the main mechanisms among the others. [224][225][226] It is plausible to tweak the characteristic bandgap transition by modifying the size of the p-domains. The increase in the size of the p-domain carbon core causes a smaller bandgap.…”
Section: Quantum Connement Effectmentioning
confidence: 99%
“…The excitation-dependent emission properties of CDs are previously reported by various mechanisms including quantum confinement effects, surface states and molecular fluorescence, electronegativity of heterogeneous atoms, and massive red edge effects. [41][42][43][44][45][46] The TEM image analysis of this study shows that CDs have similar particle size distributions and do not follow excitation-dependent emission characteristics with respect to size. The FT-IR and XPS spectra confirmed that as the N content increased and the intensity of the -OH peak decreased, the emission wavelength of CDs increased.…”
Section: Pl Emission Mechanismmentioning
confidence: 99%
“…Au nanoparticles were toxic at higher concentrations (< 1 μg/ml). [106] Furthermore, size, structure, charge, and surface morphology play crucial roles in the biocompatibility of the nanomaterials. Concentration is another crucial factor.…”
Section: Biocompatibility Of Nanomaterialsmentioning
confidence: 99%
“…The quantum dots showed the lowest toxicity, and carbon nanodots showed the highest toxic effect on all the cell lines and green gram sprouts. Au nanoparticles were toxic at higher concentrations (<1 μg/ml) [106] …”
Section: Biocompatibility Of Nanomaterialsmentioning
confidence: 99%